Preparation method and application of composite sulfide electrolyte membrane

By adopting the preparation method of composite sulfide electrolyte membrane in all solid lithium metal batteries, the problems of short battery life and low magnification caused by lithium dendrites are solved, the high mechanical properties and density of the electrolyte membrane are achieved, and the battery life is extended And increased the magnification.

CN119447439APending Publication Date: 2025-02-14WEICHAI POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411827584.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In all-solid lithium metal batteries, the formation and growth of lithium dendrites lead to short battery life and low magnification, mainly due to the intrinsic cracks of the electrolyte membrane and cracks during lithium deposition and peeling.

Method used

By adopting the preparation method of composite sulfide electrolyte membrane, lithium salt is dissolved in ether monomers and added initiators to form a prepolymerized solution, and then mixed with sulfide electrolyte powder and auxiliary solvent, and then coated on the substrate after ball milling. , stand and cure, and finally undergoes temperature isostatic pressure treatment to form a dense composite sulfide electrolyte membrane.

Benefits of technology

This method effectively inhibits the growth of lithium dendrites, improves the mechanical properties and density of the electrolyte membrane, reduces crack propagation, thereby extending the battery life and increasing the magnification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005184727600000011
    Figure HDA0005184727600000011
  • Figure HDA0005184727600000012
    Figure HDA0005184727600000012
  • Figure HDA0005184727600000013
    Figure HDA0005184727600000013
Patent Text Reader

Abstract

The invention provides a preparation method and application of a composite sulfide electrolyte membrane, and the preparation method comprises the following steps: 1) dissolving a lithium salt in an ether monomer, adding an initiator, stirring, and standing; 2) mixing the obtained prepolymerization solution with sulfide electrolyte powder and an auxiliary solvent, and carrying out ball milling to obtain slurry; 3) coating the slurry on a base material, standing and curing to obtain a first composite electrolyte membrane; continuously coating the prepolymerization solution on the first composite electrolyte membrane, standing again and curing; and carrying out warm isostatic pressing to obtain the electrolyte membrane. The prepolymer is used as a binder, so that the mechanical property of the electrolyte membrane is improved, and formation of dry cracks is reduced; the polymer wrapping the sulfide particles promotes lithium ion transmission; and the prepolymerization solution is continuously coated, so that the compactness of the composite sulfide electrolyte membrane is improved, and crack propagation is reduced, thereby inhibiting the growth of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrolyte membranes, and in particular relates to a preparation method of a composite sulfide electrolyte membrane and application thereof. Background Art

[0002] The key issue affecting the life and rate of all-solid-state lithium metal batteries is the formation and growth of lithium dendrites. When metal lithium is deposited, cracks are formed in the electrolyte near the electrode, and the cracks extend to the electrode surface to relieve stress. During the stripping process, metal lithium is prone to form voids inside the SSE, resulting in poor interface contact, high interface impedance, uneven charge distribution, and lithium dendrites extending and growing along the cracks and voids, thus causing the battery to short-circuit. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a method for preparing a composite sulfide electrolyte membrane and its application. The composite sulfide electrolyte membrane prepared by this method can solve the problems of intrinsic cracks in the electrolyte membrane and cracks during lithium deposition and stripping, and inhibit dendrite growth.

[0004] The present invention provides a method for preparing a composite sulfide electrolyte membrane, comprising the following steps:

[0005] 1) dissolving the lithium salt in the ether monomer solution, adding the initiator, stirring until completely dissolved, and standing to obtain a prepolymer solution;

[0006] 2) mixing the prepolymerization solution, sulfide electrolyte powder and auxiliary solvent, and ball milling to obtain a slurry;

[0007] 3) coating the slurry in step 2) on a substrate, allowing it to stand and solidify to obtain a first composite electrolyte membrane of sulfide solid electrolyte-polymer; continuing to coat the prepolymerization solution on the first composite electrolyte membrane, allowing it to stand and solidify again to obtain a double-layer electrolyte membrane; and performing warm isostatic pressing on the double-layer electrolyte membrane to obtain a composite sulfide electrolyte membrane.

[0008] Preferably, the ether monomer is selected from one or more of polyethylene glycol diglycidyl ether (PEGDE), 1,3-dioxolane (DOL) and 1,3,5-trioxane (TXE).

[0009] Preferably, the initiator is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(trifluoromethylsulfonyl)imide;

[0010] The concentration of the initiator in the monomer is 0.1-2 mol / L.

[0011] Preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(trifluoromethylsulfonyl)imide;

[0012] The concentration of the lithium salt in the ether monomer is 0.1-2 mol / L.

[0013] Preferably, the auxiliary solvent is selected from one or more of dimethyl carbonate, ethylene carbonate and fluoroethylene carbonate;

[0014] The viscosity of the slurry is 500-2000 mPa.s.

[0015] Preferably, the thickness of the slurry coated on the substrate is 20 μm to 200 μm;

[0016] The prepolymerization solution is continuously coated on the first composite electrolyte membrane to a thickness of 20 μm to 100 μm.

[0017] Preferably, the standing temperature is 20-30° C., the standing time is 1-5 h, and the curing temperature after standing is 50-80° C., and the time is 8-12 h.

[0018] Preferably, the pressure of the warm isostatic pressing treatment is 300-600 MPa.

[0019] The present invention provides a composite pole piece, which is prepared by the following method:

[0020] The prepolymerization solution in step 1) and the slurry in step 2) of the above technical solution are sequentially coated onto the AgC negative electrode substrate, and subjected to warm isostatic pressing to obtain a composite electrode sheet.

[0021] The present invention provides an all-solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and a composite sulfide electrolyte membrane prepared by the preparation method described in the above technical solution;

[0022] Or including the composite electrode and positive electrode described in the above technical solution.

[0023] Preferably, the positive electrode sheet is selected from a high-nickel ternary positive electrode sheet, and the surface loading of the active material in the high-nickel ternary positive electrode sheet is 12 to 20 mg / cm 2 ;

[0024] The negative electrode sheet is selected from a silver-carbon negative electrode, and the thickness of the silver-carbon layer is 3 to 20 μm.

[0025] The invention provides a preparation method of a composite sulfide electrolyte membrane, comprising the following steps: 1) dissolving a lithium salt in an ether monomer, adding an appropriate amount of an initiator, stirring until completely dissolved, and standing to obtain a prepolymerization solution; 2) mixing the prepolymerization solution, sulfide electrolyte powder and an auxiliary solvent, and ball milling to obtain a slurry; 3) coating the slurry in step 2) on a substrate, standing to solidify, and obtaining a first composite electrolyte membrane of a sulfide solid electrolyte-ion-conducting polymer; continuously coating the prepolymerization solution on the first composite electrolyte membrane, standing again to solidify, and obtaining a double-layer electrolyte membrane; and performing warm isostatic pressing on the double-layer electrolyte membrane to obtain a composite sulfide electrolyte membrane. The present invention adopts a prepolymer formed by prepolymerization as a binder for sulfide solid electrolyte powder, thereby improving the mechanical properties of the electrolyte membrane and reducing the formation of dry cracks. Compared with the traditional method, the use of binders and solvents is avoided, and the polymer that wraps the sulfide particles can conduct ions and further promote lithium ion transmission. The prepolymer solution is continuously coated to fill the gaps and cracks of the composite electrolyte membrane, and solidification is combined with warm isostatic pressing technology to improve the densification of the composite sulfide electrolyte membrane, reduce crack expansion, and thus inhibit the growth of lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram of the surface of an electrolyte membrane prepared in a comparative example of the present invention;

[0027] Figure 2 A schematic diagram of the surface of a composite sulfide electrolyte membrane prepared by the preparation method provided by the present invention;

[0028] Figure 3 is a cross-sectional scanning electron microscope image of the first electrolyte membrane in Example 1 of the present invention;

[0029] Figure 4 The figures are the test results of the specific capacities of the batteries of Examples 1 to 3 of the present invention and the comparative example. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a composite sulfide electrolyte membrane, comprising the following steps:

[0031] 1) dissolving lithium salt in ether monomer, adding appropriate amount of initiator, stirring until completely dissolved, and standing to obtain a prepolymer solution;

[0032] 2) mixing the prepolymerization solution, sulfide electrolyte powder and auxiliary solvent, and ball milling to obtain a slurry;

[0033] 3) coating the slurry in step 2) on a substrate, allowing it to stand and solidify to obtain a first composite electrolyte membrane of sulfide solid electrolyte-ion-conducting polymer; continuing to coat the prepolymer solution on the first composite electrolyte membrane, allowing it to stand and solidify again to obtain a double-layer electrolyte membrane; and performing warm isostatic pressing on the double-layer electrolyte membrane to obtain a composite sulfide electrolyte membrane.

[0034] The present invention adopts a prepolymer formed by prepolymerization as a binder for sulfide solid electrolyte powder, thereby improving the mechanical properties of the electrolyte membrane and reducing the formation of dry cracks. Compared with the traditional method, the use of binders and solvents is avoided, and the polymer that wraps the electrolyte powder can conduct ions and further promote lithium ion transmission. The prepolymer solution is continuously coated to fill the gaps and cracks of the composite electrolyte membrane, and solidification is combined with warm isostatic pressing technology to improve the densification of the composite sulfide electrolyte membrane, reduce crack expansion, and thus inhibit the growth of lithium dendrites.

[0035] The present invention dissolves lithium salt in ether monomer, then adds a proper amount of initiator, stirs until completely dissolved, and stands to obtain a prepolymerization solution.

[0036] In the present invention, the ether monomer is selected from one or more of polyethylene glycol diglycidyl ether (PEGDE), 1,3-dioxolane (DOL) and 1,3,5-trioxane (TXE).

[0037] The initiator in the present invention is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(trifluoromethylsulfonyl)imide; the concentration of the initiator in the ether monomer is 0.1-2 mol / L.

[0038] The lithium salt in the present invention is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(trifluoromethylsulfonyl)imide; the presence of the lithium salt can improve the ionic conductivity of the polymer and has a catalytic effect on the ring-opening polymerization. The concentration of the lithium salt in the ether monomer is 0.1-2 mol / L.

[0039] The present invention uses lithium salt as an initiator to initiate ring-opening polymerization of monomers; it also helps to stabilize the interface between the positive and negative electrodes. The lithium salt first decomposes to produce Lewis acid, which, as a direct initiator of the monomer, first attacks the CO bond to form an oxonium ion-cation active center to achieve ring-opening polymerization. The initiator is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bistrifluoromethylsulfonyl imide; the concentration of the initiator formed in the ether monomer is 0.1-2 mol / L.

[0040] After obtaining the prepolymer solution, the present invention mixes the prepolymer solution, electrolyte powder and auxiliary solvent, and ball mills to obtain a slurry. The auxiliary solvent is selected from one or more of dimethyl carbonate (DME), ethylene carbonate (DMC) and fluoroethylene carbonate FEC; the auxiliary solvent can regulate the solid content, the solid content is 10-50%, preferably 20-40%; it can also reduce the crystallinity of the polymer and improve the lithium transmission capacity. The sulfide electrolyte powder in the present invention is selected from one or more of binary sulfide system, argyrodite and LGPS type. The viscosity of the slurry in the present invention is 500-2000mPa.s.

[0041] The present invention coats the slurry on a substrate, and solidifies after standing to obtain a first composite electrolyte membrane of sulfide solid electrolyte-ion-conducting polymer. The substrate is PET or a silver-carbon negative electrode. The thickness of the slurry coated on the substrate is 20 to 200 μm. The standing time is 1 to 5 hours; the curing temperature after standing is 50 to 80° C.; and the curing time is 8 to 12 hours. During the curing process, the prepolymer is completely polymerized.

[0042] After obtaining the first composite electrolyte membrane, the present invention further applies the prepolymer solution to the first composite electrolyte membrane, and solidifies after standing again to obtain a double-layer electrolyte membrane. The thickness of the further coating of the present invention is 20 to 100 μm. The time of standing again in the present invention is 5 to 7 hours; the temperature of solidification after standing again is 50 to 70° C., and the time is 9 to 11 hours.

[0043] After obtaining the double-layer electrolyte membrane, the present invention performs warm isostatic pressing on the double-layer electrolyte membrane to obtain a composite sulfide electrolyte membrane. The pressure of the warm isostatic pressing treatment in the present invention is 300-600 MPa.

[0044] The present invention also provides a composite pole piece, which is prepared by the following method:

[0045] The prepolymerization solution in step 1) and the slurry in step 2) of the above technical solution are sequentially coated on the silver-carbon negative electrode substrate, and warm isostatic pressing is performed to obtain a composite electrode.

[0046] The present invention also provides an all-solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and a composite sulfide electrolyte membrane prepared by the preparation method described in the above technical solution;

[0047] Or including the composite electrode and positive electrode described in the above technical solution.

[0048] The positive electrode sheet of the present invention is selected from a high-nickel ternary positive electrode sheet, and the surface loading of the active material in the high-nickel ternary positive electrode sheet is 12-20 mg / cm 2 ;

[0049] The negative electrode sheet is selected from a silver-carbon negative electrode, and the thickness of the silver-carbon layer is 3 to 20 μm.

[0050] The all-solid-state battery provided by the present invention comprises the above-mentioned composite sulfide electrolyte membrane, so that it has excellent first discharge specific capacity, first discharge efficiency and capacity retention rate.

[0051] In order to further illustrate the present invention, a preparation method of a composite sulfide electrolyte membrane provided by the present invention and its application are described in detail below in combination with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0052] Comparative Example

[0053] Prepare 5% NBR-p-xylene glue, mix electrolyte powder and NBR in a ratio of 98:2 to make a slurry with a solid content of 45%. After stirring for a period of time with a vacuum degassing machine, apply it on the AgC negative electrode, dry it naturally, and then blow dry it at 80 degrees for 10 hours to obtain a 100-micron-thick composite AgC electrode. 2 The ternary nickel-cobalt-manganese 811 positive electrode sheet and silver-carbon negative electrode sheet are cut using a die-cutting machine. The obtained positive electrode / electrolyte membrane / negative electrode are laminated, and sulfuric acid paper and PET are used as buffer layers on both sides, and then warm isostatic pressing is performed at a pressure of 500MPa. The obtained electrode sheets are packaged and tested under the test conditions of 2.5V-4.25V. Using this method, obvious cracks and gaps will appear in the lithium deposition and stripping process, such as Figure 1 shown.

[0054] Example 1

[0055] 2 mol / L lithium bistrifluoromethylsulfonyl imide (LiTFSI) was dissolved in a 1,3-dioxolane (DOL) solution and stirred until transparent, and then 0.1 mol / L lithium difluorooxalatoborate (LiDFOB) was added and stirred until completely dissolved to obtain a transparent 1,3-dioxolane (DOL) prepolymer solution.

[0056] 1.0g of prepolymer solution was added as a binder-solvent to the sulfide electrolyte powder, and 0.5g of dimethyl carbonate was added to obtain a slurry with a solid content of 40%. The slurry was then coated on PET with a coating thickness of 200μm. After curing, the first layer of electrolyte membrane was obtained.

[0057] 1.2 g of the prepolymer solution was continuously coated onto the first layer of the electrolyte membrane with a coating thickness of 100 μm, and allowed to stand at room temperature for 6 hours. Vacuum curing was continued at 60° C., and a double-layer electrolyte membrane was obtained after 10 hours.

[0058] The obtained double-layer electrolyte membrane was subjected to warm isostatic pressing to obtain an independent supported electrolyte membrane, and the treated 12 mg / cm2 The ternary nickel-cobalt-manganese 811 positive electrode sheet and silver-carbon negative electrode sheet are cut using a die-cutting machine.

[0059] The obtained positive electrode / electrolyte membrane / negative electrode were bonded together, and sulfuric acid paper and PET were used as buffer layers on both sides, followed by warm isostatic pressing at a pressure of 500 MPa.

[0060] The obtained electrodes were packaged and tested under the test conditions of 2.5V-4.25V.

[0061] Example 2

[0062] 1.5 mol / L lithium difluorooxalatoborate (LiDFOB) was dissolved in a 1,3-dioxolane (DOL) solution at room temperature and stirred until transparent to obtain a transparent 1,3-dioxolane (DOL) prepolymer solution.

[0063] 1.0g of prepolymer solution was added as a binder-solvent to the sulfide electrolyte powder, and 0.5g of dimethyl carbonate was added to obtain a slurry with a solid content of 40%. The slurry was then coated on PET with a coating thickness of 200μm. After curing, the first layer of electrolyte membrane was obtained.

[0064] 1.2 g of the prepolymer solution was continuously coated onto the first layer of the electrolyte membrane with a coating thickness of 100 μm, and allowed to stand at room temperature for 6 hours. Vacuum curing was continued at 60° C., and a double-layer electrolyte membrane was obtained after 10 hours.

[0065] The obtained double-layer electrolyte membrane was subjected to warm isostatic pressing to obtain an independent supported electrolyte membrane, and the treated 12 mg / cm 2 The ternary nickel-cobalt-manganese 811 positive electrode sheet and silver-carbon negative electrode sheet are cut using a die-cutting machine.

[0066] The obtained positive electrode / electrolyte membrane / negative electrode were bonded together, and sulfuric acid paper and PET were used as buffer layers on both sides, followed by warm isostatic pressing at a pressure of 500 MPa.

[0067] The obtained electrodes were packaged and tested under the test conditions of 2.5V-4.25V.

[0068] Example 3

[0069] 2 mol / L lithium bistrifluoromethylsulfonyl imide (LiTFSI) was dissolved in a 1,3-dioxolane (DOL) solution and stirred until transparent, and then 0.1 mol / L lithium difluorooxalatoborate (LiDFOB) was added and stirred until completely dissolved to obtain a transparent 1,3-dioxolane (DOL) prepolymer solution.

[0070] 1.0g of prepolymer solution was added as a binder-solvent to the sulfide electrolyte powder, and 0.5g of dimethyl carbonate was added to obtain a slurry with a solid content of 40%. The slurry was then coated on silver carbon with a coating thickness of 200μm. After curing, the first layer of electrolyte membrane on AgC was obtained.

[0071] 1.2 g of the prepolymer solution was continuously coated onto the first layer of the electrolyte membrane with a coating thickness of 100 μm, and allowed to stand at room temperature for 6 hours. Vacuum curing was continued at 60° C. After 10 hours, a composite electrolyte membrane on the silver-carbon electrode was obtained.

[0072] The treated 12mg / cm 2 The ternary nickel-cobalt-manganese 811 positive electrode sheet and the integrated composite electrolyte membrane AgC negative electrode are cut using a die-cutting machine.

[0073] The obtained positive electrode sheet / composite electrolyte membrane silver-carbon negative electrode was bonded together, and sulfuric acid paper and PET were used as buffer layers on both sides, followed by warm isostatic pressing at a pressure of 500MPa.

[0074] The obtained electrodes were packaged and tested under the test conditions of 2.5V-4.25V.

[0075] The performance test methods and test results of the batteries prepared in Examples 1 to 3 and Comparative Examples of the present invention are as follows: Figure 4 shown; from Figure 4 It can be seen that: the first cycle 0.05C discharge capacity of the comparative example is 176.9mAh / g, the first efficiency is 78%; the 0.2C discharge capacity is 139.9, and the capacity is greatly reduced to 71.8mAh / g after 27 cycles; the battery prepared in Example 1 has a discharge capacity of 188mAh / g at 0.05C, and the first discharge efficiency is 82%; the 0.2C discharge capacity is 153.1mAh / g, and the capacity reaches 56.6mAh / g after 50 cycles; the battery prepared in Example 2 has a discharge capacity of 188mAh / g at 0.05C, and the first discharge efficiency is 82%; the 0.2C discharge capacity is 153.1mAh / g, and the capacity reaches 56.6mAh / g after 50 cycles; The specific capacity is 188.7 mAh / g, and the first discharge efficiency is 83.5%; the specific capacity at 0.2C discharge is 154.3 mAh / g, and the capacity reaches 108.9 mAh / g after 50 cycles, and the capacity retention rate is 70%; the battery prepared in Example 3 has a specific capacity of 189.1 mAh / g at 0.05C discharge, and an initial discharge efficiency of 85%; the specific capacity at 0.2C discharge is 155.5 mAh / g, and the capacity reaches 117.7 mAh / g after 50 cycles, and the capacity retention rate is 75.7%;

[0076] By comparing the comparative example and Example 1, the capacity and cycle performance of the soft-pack battery cell prepared by the composite membrane are significantly improved, indicating that the structure of the electrolyte composite membrane prepared by the method provided by the present invention significantly inhibits the generation of cracks and thus inhibits the formation of lithium dendrites. By comparing the amount of lithium salt and initiator in Example 1 and Example 2, the performance of the battery cell is improved; at the same time, by comparing the integration methods of the two battery cells in Example 1 and Example 3, it can be obtained that the integrated battery cell has better performance.

[0077] It can be seen from the above embodiments that the present invention provides a method for preparing a composite sulfide electrolyte membrane, comprising the following steps: 1) dissolving a lithium salt in an ether monomer, adding an initiator, stirring until completely dissolved, and standing to obtain a prepolymerization solution; 2) mixing the prepolymerization solution, sulfide electrolyte powder and an auxiliary solvent, and ball milling to obtain a slurry; 3) coating the slurry in step 2) on a substrate, standing to solidify, and obtaining a first composite electrolyte membrane of a sulfide solid electrolyte-ion-conducting polymer; continuing to coat the prepolymerization solution on the first composite electrolyte membrane, standing again to solidify, and obtaining a double-layer electrolyte membrane; and performing warm isostatic pressing on the double-layer electrolyte membrane to obtain a composite sulfide electrolyte membrane. The present invention adopts a prepolymer formed by prepolymerization as a binder for sulfide solid electrolyte powder, thereby improving the mechanical properties of the electrolyte membrane and reducing the formation of dry cracks. Compared with the traditional method, the use of binders and solvents is avoided, and the polymer that wraps the sulfide particles can conduct ions and further promote lithium ion transmission. The prepolymer solution is continuously coated to fill the gaps and cracks of the composite electrolyte membrane, and solidification is combined with warm isostatic pressing technology to improve the densification of the composite sulfide electrolyte membrane, reduce crack expansion, and thus inhibit the growth of lithium dendrites.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite sulfide electrolyte membrane, characterized in that: The following steps are involved: 1) dissolving lithium salt in an ether monomer solution, adding an initiator and stirring until completely dissolved, and standing to obtain a prepolymer solution; 2) mixing the prepolymerization solution, sulfide electrolyte powder and auxiliary solvent, and ball milling to obtain a slurry; 3) coating the slurry in step 2) on a substrate, allowing it to stand and solidify to obtain a first composite electrolyte membrane of sulfide electrolyte-ion-conducting polymer; continuing to coat the prepolymer solution on the first composite electrolyte membrane, allowing it to stand and solidify again to obtain a double-layer electrolyte membrane; and performing warm isostatic pressing on the double-layer electrolyte membrane to obtain a composite sulfide electrolyte membrane.

2. The preparation method according to claim 1, characterized in that: The ether monomer is selected from one or more of ethylene glycol diglycidyl ether, 1,3-dioxolane and 1,3,5-trioxane.

3. The preparation method according to claim 1, characterized in that: The initiator is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(trifluoromethylsulfonyl)imide; The concentration of the initiator in the ether monomer is 0.1-2 mol / L.

4. The preparation method according to claim 1, characterized in that: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(trifluoromethylsulfonyl)imide; The concentration of the lithium salt in the ether monomer is 0.1-2 mol / L.

5. The preparation method according to claim 1, characterized in that: The auxiliary solvent is selected from one or more of dimethyl carbonate, ethylene carbonate and fluoroethylene carbonate; The viscosity of the slurry is 500-2000 mPa.s.

6. The preparation method according to claim 1, characterized in that: The thickness of the slurry coated on the substrate is 20 μm to 200 μm; The prepolymerization solution is continuously coated on the first composite electrolyte membrane to a thickness of 20 μm to 100 μm.

7. The preparation method according to claim 1, characterized in that: The standing temperature is 20-30°C; the standing time is 1-5 hours; the curing temperature after standing is 50-80°C, and the time is 8-12 hours.

8. The preparation method according to claim 1, characterized in that: The pressure of warm isostatic pressing treatment is 300-600MPa.

9. A composite pole piece, characterized in that: Prepared by the following method: The prepolymer solution of step 1) and the slurry of step 2) in claim 1 are sequentially coated on the silver-carbon negative electrode substrate, and warm isostatic pressing is performed to obtain a composite electrode.

10. An all-solid-state battery, characterized in that: Comprising a positive electrode sheet, a negative electrode sheet and a composite sulfide electrolyte membrane prepared by the preparation method according to any one of claims 1 to 8; Or including the composite electrode and positive electrode as described in claim 9.

11. The all-solid-state battery according to claim 10, characterized in that: The positive electrode sheet is selected from a high-nickel ternary positive electrode sheet, and the surface loading of the active material in the high-nickel ternary positive electrode sheet is 12 to 20 mg / cm 2 ; The negative electrode sheet is selected from a silver-carbon negative electrode, and the thickness of the silver-carbon layer is 3 to 20 μm.